1996
DOI: 10.1080/01140671.1996.9513943
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fructose production by 37 cultivars of Jerusalem artichoke (Helianthus tuberosusL.)

Abstract: Improved culture of Jerusalem artichoke (Helianthus tuberosus L.) for the better production of fructose requires better performing cultivars. Analysis involving 37 cultivars originating from France or overseas showed that among the early cultivars studied, 'Grando' appear to be the richest with 193 mg/g fresh wt of dry matter (DM) and 508 mg/g DM of fructose (as fructan). For fructose production, among the late white cultivars analysed, 'Kharkov' gave the best performance with 179 mg/g fresh wt of DM, 531 mg/g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…These values show the high potential of JA for sustainable bioethanol production. The high potential of JA for sugars from tubers has also been shown by others (Curt et al, 2006;Baldini et al, 2004;Schorr-Galindo and Guiraud, 1997;Ben Chekroun et al, 1996;Barloy, 1988).…”
Section: Treatmentssupporting
confidence: 67%
“…These values show the high potential of JA for sustainable bioethanol production. The high potential of JA for sugars from tubers has also been shown by others (Curt et al, 2006;Baldini et al, 2004;Schorr-Galindo and Guiraud, 1997;Ben Chekroun et al, 1996;Barloy, 1988).…”
Section: Treatmentssupporting
confidence: 67%
“…Therefore, high and low groups were clearly separated except for few accessions, but identification of Jerusalem artichoke accessions for high or low inulin content within high or low groups was difficult. Previous study in 37 cultivars of Jerusalem artichoke could identify the genotypes with high fructose content (Grando, Kharkov, C-122, Meillo and Dubo) (Ben Chekroun et al 1996). However, there accessions were not included in this study.…”
Section: Genotypic Variability and Genotype 9 Environment Interactionsmentioning
confidence: 99%
“…Analysis involving 37 cultivars originating from France or overseas showed that among the early cultivars studied, 'Grando' appears to be the richest with 193 mg/g fresh wt of dry matter (DM) and 508 mg/g DM of fructose (as fructan) (Chekroun et al 1996 ). For fructose production, among the late white cultivars analysed, 'Kharkov' gave the best performance with 179 mg/g fresh wt of DM, 531 mg/g DM of fructose and 710 mg/g DM of total carbohydrates.…”
Section: Fructose Productionmentioning
confidence: 99%
“…Groot Wassink and Fleming ( 1980 ) found that Kluyveromyces fragilis inulase (β-fructofuranosidase) to be a better alternative to Saccharomyces cerevisiae invertase presently used in industry for fermentation. H. tuberosus was used as a raw material for the production of motor fuel alcohol during the Second World War and had been sporadically used for this purpose until now (Chekroun et al 1996 ).…”
Section: Biogas Biofuel: Ethanol Biodiesel Productionmentioning
confidence: 99%